Plausible Last Interglacial Antarctic Ice Sheet Changes Do Not Fully Explain Antarctic Ice Core Water Isotope Records - Huiling Zou; Louise C. Sime; Nancy A. N. Bertler; Elizabeth D. Keller; Eric W. Wolff (Geophysical Research Letters)
Abstract Antarctic ice cores can help determine ice mass loss from the Antarctic Ice Sheet (AIS) during past warm periods. We compile Last Interglacial (LIG) δ18O measurements from eight Antarctic cores and compare these to new isotope‐enabled LIG simulations, which explore three plausible LIG AIS elevation and extent scenarios. We find that these simulations capture less than 10% of East Antarctic core‐mean δ18O changes. Although our simulations do not fully explain the changes, they capture some inter‐core geographical δ18O variations. Some LIG AIS configurations show higher skill than PI AIS configurations in simulating the inter‐core differences. The remaining discrepancies between the simulated and observed core‐mean water isotope changes suggest that LIG simulations also need to include the influences of reduced Antarctic sea ice, a warmer Southern Ocean, and resultant shifts in vapor source regions to produce a more satisfactory match to δ18O observed at ice core sites.